The Queen of education : - Johnson, LouAnne (Jossey-Bass, 2004)
Wanted: A Queen of Education. Candidate must be able to take decisive action, cut through red tape, deflate the bureaucratic bloat, wrestle with the diagnostic nightmare of ADHD, and refuse to sell out her students to the corporate fat cats. Though we have "education presidents" who give lip service to fixing schools?what we really need is a Queen of Education who will get the job done. Anyone searching for such a candidate would put LouAnne Johnson's resume on the top of the stack of likely applicants. LouAnne Johnson is the gutsy ex-marine turned teacher who has wrestled with tough kids and even tougher adults. Her life inspired the movie Dangerous Minds - which was based on her book My Posse Don't Do Homework. Johnson's knack for finding original solutions to intractable problems has not only made her an exemplary teacher but a popular speaker on the lecture circuit. In this engaging book, "Queen" LouAnne offers her down-to-earth advice about fixing schools. Johnson makes no secret about the fact that she is fed up with an educational system that is too quick to label and write off children who don?t fit the mold. Among her royal rules for fixing the system: no class shall have more than 20 students, all elected representatives must teach in a public school classroom for two weeks, and the testing frenzy must stop this very second! LouAnne is a passionate advocate for schools that are smaller, healthier, more humane, and more attuned to different learning styles. With humor and good sense, she shows how a compassionate teacher or parent can cut through the red tape and make a crucial difference in the life of a child.